Economic crisis in the Middle East and North Africa - Marek D\~nabrowski; Marta Domínguez-Jiménez (Bruegel, 2021)
In the 2010s, the economic situation in the Middle East and North Africa (MENA) deteriorated as a result of lower oil and other commodity prices, a new round of domestic political instability, continuous intra-regional conflicts, stalled economic and governance reforms and, finally, the COVID-19 pandemic.The growth of real GDP, which slowed after the global financial crisis of 2008-2009, further decelerated in the second half of the 2010s and became negative in 2020 as result of the COVID-19 shock. Fiscal balances have deteriorated, even in the oil-exporting countries, and public debt has grown rapidly. MENA countries continue to face numerous long-term socio-economic and institutional challenges including high unemployment (especially youth unemployment), low female labour-market participation rates, the poor quality of education, costly and ineffective public sectors, high military and security spending, high energy subsidies and trade protectionism. Only comprehensive long-term reform programmes can address these challenges.The European Union is MENA's second largest trading partner after the region itself, and is one of two main sources of foreign direct investment and a major aid donor. However, given the critical importance of the MENA region to its own security and stability, the EU's engagement in conflict resolution and in supporting economic and political transformation of the region is insufficient and should be intensified. The EU should also update and upgrade its existing association agreements with the countries of the Southern and Eastern Mediterranean, including their free trade provisions.
Keywords: 330